Faithfulness and fidelity across identities and contexts for SOTL in the global South - KC Lee; Zach Simpson (University of Johannesburg, 2021)
Issue 5.2 of SOTL in the South features four peer-reviewed articles, one reflective piece and one book review. The peer-reviewed articles include two articles about broader concerns related to the scholarship of teaching and learning in higher education, namely the discursive and negotiated work of producing SoTL work and the importance of considering diverse worldviews regarding research ethics. In addition, there are two detailed accounts of instances of SoTL, one from Lesotho, addressing the challenges facing students from rural contexts, and the other from South Africa, investigating the implementation of collaborative learning in a fourth-year social work classroom. The issue concludes with a reflection on an action-oriented workshop held in Aotearoa New Zealand aimed at increasing the number of Māori and Pasifika academics, and a review of The Bloomsbury Handbook of the Internationalization of Higher Education in the Global South.